(untitled) (Revista da Faculdade de Odontologia - UPF, 2016)
Introduction: The WHO classifies ameloblastoma as a benign epithelial odontogenic tumor without odontogenic ectomesenchyme with locally invasive behavior and high recurrence rate. It represents 1% of oral tumors, primarily affecting the posterior mandible. Generally slow growing and asymptomatic, it can perforate the cortical bone, reabsorb and move teeth, and cause facial asymmetry. Classification may be given, according to clinical and radiographic aspects, as solid or multicystic, cystic, and peripheral ameloblastoma. Objectives: To report a case of multicystic ameloblastoma treated with marginal resection of the mandible. Case report: 34-year-old patient referred for assessment of multiloculated radiolucent lesion involving areas of the body, angle, and right mandibular ramus, revealing by histopathological examination the diagnosis of ameloblastoma. The patient underwent resection surgery and reconstruction plate fixation for layer maintenance. Eighteen months after surgery, there were no clinical or radiographic signs. Final considerations: The interpretation of clinical and imaging data of patients with ameloblastoma is essential for early diagnosis and effective treatment of the lesion. Follow-up with regular visits is an essential part of treatment, considering their local aggressiveness and high recurrence rate.